2022
DOI: 10.1186/s12959-022-00430-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of the PAI-1 4G/5G polymorphism in Chinese patients with venous thromboembolism

Abstract: Background Venous thromboembolism (VTE) is a life-threatening cardiovascular syndrome that characterized by the imbalance of hemostasis and thrombosis and the formation of thrombi in the blood vessels. The aim of this study was to elucidate the clinical impact of the PAI-1 4G/5G polymorphism in Chinese patients with VTE. Methods A total of 169 subjects (89 VTE, 10 hyperbilirubinemia, 10 hyperlipidemia and 60 healthy controls) were recruited at Peki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 56 publications
(56 reference statements)
0
9
0
Order By: Relevance
“…Here, we found no association between the genetically determined PAI-1 concentration and the risk of VTE, DVT, and PE. Zhang et al (2020) and Wang et al (2022) revealed the PAI-1 4G/5G polymorphism associated with the risk of the onset of VTE in East Asian ancestry, but the causal relationship between serum PAI-1 levels and VTE risk was not recognized in our study, probably because the GWAS data we assessed were generated from European ancestry. Because of variances in gene linkage disequilibrium among races, SNPs indicating PAI-1 levels in GWAS studies of European populations do not reflect PAI-1 levels in other races.…”
Section: Discussionmentioning
confidence: 64%
“…Here, we found no association between the genetically determined PAI-1 concentration and the risk of VTE, DVT, and PE. Zhang et al (2020) and Wang et al (2022) revealed the PAI-1 4G/5G polymorphism associated with the risk of the onset of VTE in East Asian ancestry, but the causal relationship between serum PAI-1 levels and VTE risk was not recognized in our study, probably because the GWAS data we assessed were generated from European ancestry. Because of variances in gene linkage disequilibrium among races, SNPs indicating PAI-1 levels in GWAS studies of European populations do not reflect PAI-1 levels in other races.…”
Section: Discussionmentioning
confidence: 64%
“…Many research are looking into the relationship between PAI-1 4G/5G polymorphisms and a variety of disorders, such as thrombosis (Zhang et al, 2020a), systemic lupus erythematosus (Anaya-Macias et al, 2020), thyroid eye disease (Katko et al, 2021), metabolic syndrome (Zhang et al, 2020b) and many more. Previous research from our center has shown that the PAI-1 4G/ 5G polymorphism may be useful for determining the prognosis of Chinese patients with venous thromboembolism (Wang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the field of allergic diseases had few Frontiers in Genetics frontiersin.org corresponding reports. TaqMan-MGB qPCR offered a reliable and affordable method for investigating SNPs with allergy disorders (Wang et al, 2021;Jin et al, 2022;Wang et al, 2022). Using this technology, we initially discovered that patients with allergic cough had a different distribution of the PAI-1 rs1799762 gene than healthy people.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, the application prospects of PAI-1 in clinical practice are very broad, not only in gynecological malignant tumors, but be of great signi cance for the screening, diagnosis, evaluation of treatment responses, and prediction of prognosis for various diseases. PAI-1 is an important factor in regulating the formation of thrombi in the blood vessels, and it plays an important role in the prevention and treatment of cardiovascular diseases.By inhibiting the PAI-1, it can effectively prevent and treat the occurrence of some diseases, such as cardiovascular diseases and stroke [17] .A great deal of studies have also shown that serum PAI-1 level is closely related to the growth, metastasis, and invasion of tumors. At the same time, PAI-1 level can be used to screen early stage of lung cancer and predict treatment response of breast cancer [18] .…”
Section: Discussionmentioning
confidence: 99%